Influence of Superovulatory Protocols on In Vitro Production of Nellore (Bos indicus) Embryos - Monteiro, F. M. [UNESP]; Ferreira, M. M. G. [UNESP]; Potiens, J. R.; Eberhardt, B. G. [UNESP]; Trinca, L. A. [UNESP]; Barros, C. M. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
There are indications in the literature that delaying the period between ovarian superestimulation and ovum pick up (OPU) would induce follicles to a condition of initial atresia, which could be beneficial to oocyte development. In this work, we compared three protocols for OPU and in vitro production (IVP) of embryos, in Nellore cattle. Nellore cows (n = 18) were randomly allocated in three groups: Group 1 (OPU), Group 2 [Follicle stimulating hormone (FSH) and OPU] and Group 3 (FSH deprivation and OPU). Three OPUs were performed, and the animals were switched to a different group each time (crossover), in such a way that at the end of the experiment all cows received the 3 protocols. At random stage of the oestrous cycle (D-2), all follicles >= 6 mm were aspirated to induce a new follicular wave 2 days afterwards (D0). In Group 1, OPU was performed on D2 and oocytes were processed to IVP. In Group 2, starting on D0, cows were superstimulated (FSH, Folltropin (R), 30 mg administered daily, i.m., during three consecutive days, total dose = 180 mg), and 6 h after the last FSH dose, they received exogenous luteinizing hormone (LH) (12.5 mg, i.m., Lutropin (R), D3). The OPU was performed 6 h after LH administration, i.e. 12 h after the last dose of FSH. Animals in Group 3 received the same treatment as those in Group 2, except that LH was administered 42 h after the last dose of FSH, and OPU occurred 6 h later. Therefore, in this group, follicles were deprived of FSH at 48 h. Both cleavage and blastocyst rates were similar (p > 0.05, ANOVA) among oocytes from Groups 1, 2 and 3, respectively: 77.4% (144/185) and 42.70% (79/185); 75.54% (105/139) and 31.65% (44/139); 63.52% (101/159) and 33.33% (53/159). However, hatched blastocyst rate was higher (p < 0.01) in Group 1 (30.27%, 56/185) when compared with Group 2 (11.51%, 16/139) or 3 (15.72%, 25/159). It is concluded that, contrary to previous work on European breeds (Bos taurus), ovarian superstimulation associated with deprivation of FSH and OPU (Group 3) did not increase IVP of Nellore embryos (Bos indicus). on the contrary, the highest hatched blastocyst rates were observed in oocytes from non-superstimulated cows.